Analisis Hadith-Hadith Tentang Dosa-Dosa Besar Dalam Kitab Al-Kaba'Ir Li Al-Dhahabi - Mamat, Abd Rahman (2014)
The study was undertaken to analyse the hadiths on cardinal sins as found in the literature al-kaba’ir. Two versions of different books has been spread, which contain hadiths that is da‘if as well as fake within the content of al-kaba’ir that resulted in confusion among the muslim. Thus, this research is aimed to give the needed exposure in order to eliminate the confusion that has been arisen. A widely used source of reference and teaching in many mosques and rnusolla. Itis aimed to investigate the perplexity in determining the authenticity of the hadiths in al-kaba’ir and those claimed by the imam al-dhahabi. The study also examined evidences accrcditing the expertise of al-dhahabi in the discipline of hadiths. Six topics on mortal sins studied were the sins of shirk (the unforgivable crime of worshipping anyone and anything other than the singular god, i.E. Allah), the sins of killing, sins of practicing witch crafts, sins of not praying or performing the five times solah, sins of not paying the zakat and sins of being disrespectful to parents. A qualitative approach was used in this research. Data gathered was analysed, inductively and deductively. A total of 42 hadiths were analysed and the findings showed that 24 hadiths were found to authentic, sahih from the sanad and matan perspectives. 14 other hadiths were hasan lidhatih while 4 other hadiths were found to be darf. On the other hand it was found that al-dhahabi recorded 76 mortal sins.